Easily available ECG and echocardiographic parameters for prediction of left atrial remodeling and atrial fibrillation recurrence after pulmonary vein isolation: A multicenter study. (5th May 2021) - Moreno‐Weidmann, Zoraida; Müller‐Edenborn, Björn; Jadidi, Amir S.; Bazan‐Gelizo, Victor; Chen, Juan; Park, Chan‐il; Vivekanantham, Hari; Rodriguez‐Font, Enrique; Alonso‐Martín, Concepción; Guerra, José M.; Campos‐García, Bieito; Espinosa‐Viamonte, Hildemari; et al.
Abstract: Background: The assessment of noninvasive markers of left atrial (LA) low‐voltage substrate (LVS) enables the identification of atrial fibrillation (AF) patients at risk for arrhythmia recurrence after pulmonary vein isolation (PVI). Methods: In this prospective multicenter study, 292 consecutive AF patients (72% male, 62 ± 11 years, 65% persistent AF) underwent high‐density LA voltage mapping in sinus rhythm. LA‐LVS (<0.5 mV) was considered as significant at 2 cm 2 or above. Preprocedural clinical electrocardiogram and echocardiographic data were assessed to identify predictors of LA‐LVS. The role of the identified LA‐LVS markers in predicting 1‐year arrhythmia freedom after PVI was assessed in 245 patients. Results: Significant LA‐LVS was identified in 123 (42%) patients. The amplified sinus P‐wave duration (APWD) best predicted LA‐LVS, with a 148‐ms value providing the best‐balanced sensitivity (0.81) and specificity (0.88). An APWD over 160 ms was associated with LA‐LVS in 96% of patients, whereas an APWD under 145 ms in 15%. Remaining gray zones improved their accuracy by introduction of systolic pulmonary artery pressure (sPAP) of 35 mmHg or above, age, and sex. According to COX regression, the risk of arrhythmia recurrence 12 months following PVI was twofold and threefold higher in patients with APWD 145–160 and over 160 ms, compared to APWD under 145 ms. Integration of pulmonary hypertension further improved the outcome prediction in the intermediate APWD group: Patients with APWD 145–160 ms and normal sPAP had similar outcome than patients with APWD under 145 ms (hazard ratio [HR] 1.62, p = .14), whereas high sPAP implied worse outcome (HR 2.56, p < .001). Conclusions: The APWD identifies LA‐LVS and risk for arrhythmia recurrence after PVI. Our prediction model becomes optimized by means of integration of the pulmonary artery pressure.